SURANJANA (COLCHICUM LUTEUM BAKER.) - A RHIZOMATIC PLANT - Reeta, *Malviya; Ravindra, Sharma; Sharma, Tarun; Sumit, Nathani; Kotecha, Meeta (AYUSHDHARA, 2015)
The drug with the name ‘Suranjan’ commonly in practice today, is the dry extract of underground part of Colchicum luteum Baker. Medicinal use of Suranjana is majorly seen in Unani system of medicine. Unani practitioners have been using this drug as digestive, laxative, analgesic and aphrodisiac agent. It is a proven analgesic and a potent uricosuric drug. Its chief active principle colchicine is a well known drug to treat gout. Hence this drug enjoys an important status in Unani system of medicine and literature. In Ayurvedic literature it has been first mentioned by Acharya Shankar Dutt Gond, in his Shanker Nighantu in 1935 A.D. so its addition to Ayurvedic literature is a recent one and its references in Ayurvedic literature is not in abundance. According to Ayurvedic literature, Suranjana is Tikta (bitter) and Katu (pungent) in Rasa (taste); Laghu (light) and Ruksha (dry) in Guna (properties); Ushna (hot) in Virya (potency); and Katu in Vipak (metabolism). Because of its properties it is pacifies Vata Kapha dosh and hence is a very good anti inflammatory agent. Modern researches on colchicines prove it as an antioxidant, anti inflammatory, antifungal and antibacterial drug. Some research also projects its anti cancer activities. This paper is an attempt to bring this effective drug to lime light by describing palliative, therapeutic and other uses of Colchicum luteum Baker.